Physical quality of an Oxisol under no-tillage subjected to different cropping systems - Seben Junior, Getulio de Freitas; Corá, José Eduardo; Lal, Rattan (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the physical quality of an Oxisol under no-tillage subjected to different crop rotations and crop sequences. The experiment was carried out in a clayey Oxisol, during six years, in a randomized complete block design, with strip plots and three replicates. The following physical indicators of soil quality were evaluated: soil density and carbon content, as well as mean weight diameter and tensile strength of aggregates. Treatments consisted of three summer crop rotations – corn/corn (Zea mays), soybean/soybean (Glycine max), and soybean/corn – and of seven second crops (crop sequences) – corn, sunflower (Helianthus annuus), oilseed radish (Raphanus sativus), pearl millet (Pennisetum americanum), pigeon pea (Cajanus cajan), grain sorghum (Sorghum bicolor), and sun hemp (Crotalaria juncea). Crop rotations and sequences did not affect soil carbon contents. Corn, as a summer crop, increased the tensile strength and mean weight diameter of aggregates, similarly to pearl millet and sorghum as second crops. Soybean/corn rotation with sun hemp as a second crop increases soil physical quality, promoting higher tensile strengths and lower soil densities.